Treating acute cystitis with biodegradable micelle-encapsulated quercetin - Wang, Bi Lan (Dove Medical Press, 2012)
Intravesical application of an anti-inflammatory drug is an efficient strategy for acute cystitis therapy. Quercetin (QU) is a potent anti-inflammatory agent; however, its poor water solubility restricts its clinical application. In an attempt to improve water solubility of QU, biodegradable monomethoxy poly(ethylene glycol)-poly(ɛ-caprolactone) (MPEG-PCL) micelles were used to encapsulate QU by self-assembly methods, creating QU/MPEG-PCL micelles. These QU/MPEG-PCL micelles with DL of 7% had a mean particle size of <34 nm, and could release QU for an extended period in vitro. The in vivo study indicated that intravesical application of MPEG-PCL micelles did not induce any toxicity to the bladder, and could efficiently deliver cargo to the bladder. Moreover, the therapeutic efficiency of intravesical administration of QU/MPEG-PCL micelles on acute cystitis was evaluated in vivo. Results indicated that QU/MPEG-PCL micelle treatment efficiently reduced the edema and inflammatory cell infiltration of the bladder in an Escherichia coli-induced acute cystitis model. These data suggested that MPEG-PCL micelle was a candidate intravesical drug carrier, and QU/MPEG-PCL micelles may have potential application in acute cystitis therapy.